已知P(A)=0.4,P(B)=0.7,P(A∪B)=0.5,则P(AB)=( )
A: 0.6
B: 0.5
C: 0.7
D: 0.3
A: 0.6
B: 0.5
C: 0.7
D: 0.3
A
举一反三
- 已知P(A)=0.4,P(AB̅)=0.3,P(B)=0.5,则P(AB)=? A: 0.9 B: 0.8 C: 0.7 D: 0.6
- 设P(A)=0.7, P(A-B)=0.3,则P(AB)c=( ) A: 0.6 B: 0.4 C: 0.7 D: 0.5
- 已知P(A)=0.6,P(B)=0.7,P(A+B) =0.8则P(AB)=( ) A: 0.3 B: 0.4 C: 0.5 D: 0.6
- 已知P(A)+P(B)=0.9,P(AB)=0.2,则P(AB)+P(AB)等于()。 A: 0.3 B: 0.4 C: 0.5 D: 0.6 E: 0.7
- 已知P(A)=0.7,P(B)=0.5,P(AB)=0.4,则P(A∪B)=____。
内容
- 0
已知P(A)=0.3, P(B)=0.4, P(A|B)=0.5, 则P(B|AUB) A: 0.6 B: 0.7 C: 0.8 D: 0.9
- 1
设A,B为随机事件,P(A)=0.7,P(A-B)=0.3,则P()=(). A: 0.4 B: 0.5 C: 0.6 D: 0.7
- 2
设P(A)=0.4, P(A∪B) =0.7, 若A与B互不相容, 则P(B)= ( ) A: 0.3 B: 0.5 C: 0.6 D: 0.7
- 3
已知事件A和B的P(AB)=0.4,P(A)=0.8,则P(B|A)=() A: 0.5 B: 0.6 C: 0.65 D: 0.7
- 4
已知A,B为互斥事件,且P(A)=0.4,P(B)=0.2,P(AB=0.1),则P(A∪B)=() A: 0.4 B: 0.5 C: 0.6 D: 0.7